INOVASI DALAM MANAJEMEN HUBUNGAN MASYARAKAT UNTUK WILAYAH HUTAN TROPIS LEMBAB : PENDEKATAN TERPADU DARI PERENCANAAN HINGGA PARTISIPASI MASYARAKAT - Diyah Ayu Kristianti; Shofiyyah, Alya; Gede, Ni Luh; Warman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Moist tropical forests are vital but threatened ecosystems. Traditional forest management often ignores local communities, which leads to conflict and environmental damage. This research proposes an integrated approach that includes community participation and conflict resolution to improve conservation and prosperity. This study offers practical recommendations for more sustainable and equitable forest management, emphasizing the urgent need for innovative strategies to protect these critical environments. This type of research is qualitative with library study data collection techniques. Based on the study, it is known that innovation in Community Relations Management for humid tropical forest areas requires a holistic and integrated approach that includes careful planning and active community participation. By embracing inclusive engagement strategies, integrating traditional knowledge, leveraging technology to overcome logistical barriers, investing in local capacity, and facilitating multi-stakeholder collaboration, Community Relations efforts can be significantly enhanced. This comprehensive approach not only addresses the region's unique challenges, but also fosters trust, respect, and effective communication between external organizations and local communities, ultimately supporting sustainable development and conservation goals.